Penerapan Sistem Informasi Manajemen Puskesmas (SIMPUS) Berbasis Web Di Puskesmas Pajang Surakarta - Nilawati, Lely Noor; , Sri Sugiarsi, SKM, M.Kes; , Sri Darnoto S.KM M.PH (2016)
Primary Health Care Pajang Surakarta has implemented a management information system Primary Health Care (SIMPUS) web-based, the application is still major obstacles obedience drug input and delays in reporting. The purpose of this study was to investigate the application of health management information system in Primary Health Care Pajang Surakarta. This type of research is qualitative descriptive study. The population in this study were 10 people from health personnel. The informants are 6 informant and 2 informants as triangulation that was taken by purposive sampling technique. The data in this study is qualitative data in the form of descriptions about the picture SIMPUS Web-based of the application. Analysis of the study with 3 stages of data reduction, data presentation and conclusion. The results showed that the flow of patient data collection at the start of registration, medical services, investigation and pharmacies. Input data by entering a username and password, constraints on drug data input. The data processing is done using computers. Data Reporting contain about LB1 reporting, infectious diseases, LPLPO, the data STP, reporting askes.